2007
DOI: 10.2337/dc07-0203
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance

Abstract: OBJECTIVE -We examined the relationship of in vivo insulin sensitivity to the components of the metabolic syndrome and biomarkers of endothelial dysfunction in youth. RESEARCH DESIGN AND METHODS -Subjects included 216 youths (8 -19 years of age) who participated in a 3-h hyperinsulinemic-euglycemic clamp.RESULTS -Independent of race, the frequencies of central obesity, high triglycerides, low HDL, high blood pressure, impaired fasting glucose, and impaired glucose tolerance were significantly higher (P Ͻ 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
52
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 38 publications
(33 reference statements)
11
52
0
5
Order By: Relevance
“…Several meta-analyses in this population showed similar results for other CRFs, such as lipid levels (triglyceride and LDL cholesterol) (19) and blood pressure (20). As a consequence, the importance of good planning and optimization of aerobic exercise on CRF benefits (reductions in hypertension, triglyceride concentrations, LDL cholesterol concentrations, and insulin resistance markers) has been highlighted (37).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Several meta-analyses in this population showed similar results for other CRFs, such as lipid levels (triglyceride and LDL cholesterol) (19) and blood pressure (20). As a consequence, the importance of good planning and optimization of aerobic exercise on CRF benefits (reductions in hypertension, triglyceride concentrations, LDL cholesterol concentrations, and insulin resistance markers) has been highlighted (37).…”
Section: Discussionsupporting
confidence: 60%
“…score (R0.5) (36). However, visceral fat seems to be a better predictor of insulin resistance independent of total body fat (7,37). Unfortunately, abdominal fat values were not reported by all studies, which was why we could not investigate this in the current study.…”
Section: Discussionmentioning
confidence: 77%
“…46, 47 Lee et al showed that in Caucasian, but not in African, youths, (8-19 years) IR was significantly associated with the biomarkers of endothelial dysfunction, ICAM-1 and E-selectin. 45,48 This study also suggested that racial differences in circulating adhesion molecules are already present during childhood. Although uncertain, it is plausible that higher visceral adipose tissue in Caucasians compared to African Americans may in part explain this racial differential in endothelial biomarkers.…”
supporting
confidence: 55%
“…39 Recent studies provide evidence that overweight and obese children present with increased circulating levels of sICAM-1 and VCAM-1, 22,40-43 while only one study suggests that there is no difference between obese and normal weight children. 44 Overweight children have elevated levels of circulating soluble adhesion molecules closely related to excess body fat, 45 body mass index (BMI) and insulin resistance (IR). 22 It should be noted that IR is a well-established consequence of excess weight and obesity.…”
mentioning
confidence: 99%
“…Belo Horizonte, MG intROduçãO A resistência à insulina (RI) representa uma alteração metabólica de etiologia genética e ambiental caracterizada por resposta anormal dos tecidos periféricos à ação da insulina circulante 1 . Ela tem sido considerada a base fisiopatológica entre as diversas alterações presentes na síndrome metabólica, como a hipertensão arterial, a intolerância à glicose, o diabetes, as dislipidemias e a presença de estados pró-inflamatórios 2 .…”
Section: Nutricionista -Doutoranda Em Clínica Médica -Limed -Laboratóunclassified